Heavy metal immobilization by cost-effective amendments in a contaminated soil: Effects on metal leaching and phytoavailability - Houben, David; Pircar, Jonathan; Sonnet, Philippe (Journal of geochemical exploration, 2012)
The combination of revegetation and application of stabilizing soil amendments on heavy metal-contaminated soils is generally considered to be a promising alternative to expensive classical remediation techniques. Here, we simultaneously investigated the effects of six cost-effective amendments (CaCO3, iron grit, fly ash, manure, bentonite and bone meal) on Cd, Zn and Pb leaching and phytoavailability (assessed using white lupin, Lupinus albus L.). The Cd and Zn leaching was reduced by all amendments mainly due to alkalinity increase. The Pb leaching was strongly affected by the dissolved organic carbon (DOC) release. Therefore, bone meal and manure treatments, which highly increased DOC concentrations in leachates, increased the flow-weighted mean Pb concentrations by 2.3 and 16 times, respectively. Surprisingly, while iron grit induced strong Cd and Pb leaching reductions, this amendment doubled Cd and Pb concentrations in shoots of white lupin. Conversely, the addition of bone meal reduced Pb concentrations in shoots by 74%, probably because organo-Pb complexes (predicted using Visual MINTEQ) were largely dominant in solution. Overall, the addition of CaCO3 offered the best compromise as it successfully reduced both the leaching and the phytoavailability of the three considered metals. Our results demonstrate the efficacy of several amendments while stressing the need to measure simultaneously the leaching and the phytoavailability of metals induced by each amendment. ► We study the effects of amendments on Cd, Zn and Pb leaching and phytoavailability. ► pH controls Cd and Zn leaching while DOC controls Pb leaching. ► Iron grit highly lowers metal leaching but doubles Cd and Pb phytoavailability. ► Bone meal and manure lower metal phytoavailability but strongly increase Pb leaching. ► CaCO3 appears to be the most effective amendment.